Recent advances in nanomedicine preparative methods and their therapeutic potential for colorectal cancer: a critical review - Jain, Arinjay; Bhattacharya, Sankha (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is a prevalent malignancy that affects a large percentage of the global population. The conventional treatments for CRC have a number of limitations. Nanoparticles have emerged as a promising cancer treatment method due to their ability to directly target cancer cells and regulate drug release, thereby enhancing therapeutic efficacy and minimizing side effects. This compilation examines the use of nanoparticles as drug delivery systems for CRC treatment. Different nanomaterials can be used to administer anticancer drugs, including polymeric nanoparticles, gold nanoparticles, liposomes, and solid lipid nanoparticles. In addition, we discuss recent developments in nanoparticle preparation techniques, such as solvent evaporation, salting-out, ion gelation, and nanoprecipitation. These methods have demonstrated high efficacy in penetrating epithelial cells, a prerequisite for effective drug delivery. This article focuses on the various targeting mechanisms utilized by CRC-targeted nanoparticles and their recent advancements in this field. In addition, the review offers descriptive information regarding numerous nano-preparative procedures for colorectal cancer treatments. We also discuss the outlook for innovative therapeutic techniques in the management of CRC, including the potential application of nanoparticles for targeted drug delivery. The review concludes with a discussion of current nanotechnology patents and clinical studies used to target and diagnose CRC. The results of this investigation suggest that nanoparticles have great potential as a method of drug delivery for the treatment of colorectal cancer.